Nonalcoholic Steatohepatitis: An Evolving Diagnosis - Brent A Neuschwander-Tetri (Canadian Journal of Gastroenterology)
Nonalcoholic steatohepatitis (NASH) is a histological diagnosis applied to a constellation of liver biopsy findings that develop in the absence of alcohol abuse. Steatosis, a mixed cellular inflammatory infiltrate across the lobule, evidence of hepatocyte injury and fibrosis are the findings that can be seen. This entity is often identified during evaluation of elevated aminotransferases after exclusion of viral, metabolic and other causes of liver disease. Obesity is a major risk factor for NASH. The role of diabetes is less certain, although evidence is accumulating that hyperinsulinism may play an important pathophysiological role. Patients sometimes suffer from right upper quadrant abdominal pain and fatigue; examination may reveal centripetal obesity and hepatomegaly. Although patients are often discovered because of persistent aminotransferase elevations, these enzymes can be normal in NASH. When they are elevated, the alanine aminotransferase level is typically significantly greater than the aspartate aminotransferase level. This can be particularly helpful for excluding occult alcohol abuse. Imaging studies identify hepatic steatosis when the amount of fat in the liver is significant; however, imaging does not distinguish benign steatosis from NASH. Ultimately a liver biopsy is needed to diagnose NASH. The biopsy may be useful for establishing prognosis based on the presence or absence of fibrosis and for excluding other unexpected causes of liver enzyme elevations. Weight loss is the mainstay of treatment for obese patients. About 15% to 40% of NASH patients develop fibrosis; how many of these cases progress to cirrhosis is unknown, but about 1% of liver transplants are performed with a pretransplant diagnosis of NASH.